Intervenções fisioterapêuticas e de terapia ocupacional para participação social de crianças e adolescentes com transtorno do espectro autista: revisão integrativa - Oliveira, Amanda Araújo de (Brasil, 2022)
Objective: To identify and demonstrate the scientific evidence that encompasses physical therapy and OT interventions to promote the social participation of children and adolescents with ASD. Method: This is an integrative literature review study. The searches started from February 5, 2022 to May 10, 2022, in the following databases: Google Scholar, Scielo, PEDro, PubMed and MedLine. Results: Twelve studies were selected. Of these, 1 exploratory research and 7 randomized and non-randomized clinical trials. The studies applied interventions, techniques and methods with the main outcome of improving development, especially in social participation for children and adolescents diagnosed with ASD, aged between 2 and 12 years, of both sexes. Conclusion: The application of structured programs composed of individual and collective activities with aerobic dances, games, games and even sports are effective for improving social performance, interaction between colleagues and professionals, self-confidence, socialization, and especially in social participation, both in an home and in schools.